1993
DOI: 10.1002/1520-6750(199302)40:1<117::aid-nav3220400108>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

The conditionalp-center problem in the plane

Abstract: An algorithm is given for the conditional p-center problem, namely, the optimal location of one or more additional facilities in a region with given demand points and one or more preexisting facilities. The solution dealt with here involves the minimax criterion and Euclidean distances in two-dimensional space. The method used is a generalization to the present conditional case of a relaxation method previously developed for the unconditional p-center problems. Interestingly, its worst-case complexity is ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Choice of Metric. Many papers on geometric location theory have dealt with continuous sets F of feasible placements, including [2,5,13,14,16,21,37,38,39,62,63,64]. In the majority of these papers, distances are measured according to the L 1 metric.…”
Section: Geometric Facility Locationmentioning
confidence: 99%
“…Choice of Metric. Many papers on geometric location theory have dealt with continuous sets F of feasible placements, including [2,5,13,14,16,21,37,38,39,62,63,64]. In the majority of these papers, distances are measured according to the L 1 metric.…”
Section: Geometric Facility Locationmentioning
confidence: 99%
“…There are also studies in the literature dealing with the point-conditional location problem in the plane. (See for example, [5,6]. )…”
Section: Introductionmentioning
confidence: 99%
“…The results have indicated that the algorithm can consistently generate solutions with a limited number of relocations that improve on the corresponding time-invariant optimal solutions. Future work will focus on adapting the ideas of this paper to other variants of the p-center problem, such as the capacitated p-CP (Kramer et al, 2018), the weighted p-CP (Chen and Handler, 1993), the conditional p-CP (Berman and Drezner, 2008), the α-neighbor p-CP (Chen and Chen, 2013).…”
Section: Discussionmentioning
confidence: 99%